Pengaruh Penambahan Aras Ekstrak Kubis Sortir dan Lama Pemeraman Terhadap Kandungan Nutrisi Silase Ikan - Cahya Setya Utama; Sri Sumarsih (JURNAL KESEHATAN, 2010)
This research aim to study the influence of addition of level of cabbage pickle sort to content of nutrisi silase fish. Research executed in two Laboratory that is Technological Laboratory of Food of Livestock. andLaboratory of Science of Livestock Food, Majors of Nutrisi and Livestock Food, Faculty Of Veterinary of University of Diponegoro Semarang. Research Activity by three phase. First phase early making of cabbagecondensation that is by cleaning cabbage beforehand, later;then cut to pieces to minimize and enhanced salt 2,5Yo from fresh weight of cabbage. Afterwards, mingled called a meeting to order anaerob during 4 day tobe taken by its condensation (starter). count of Fish, later;then steamed and extorted obstetrical until aimya lose the. Molasses as much 15% from fresh weight of fish and enhanced by starter of cabbage condensation12,5yo, 15Yo and l7,5Yo from fresh weight of fish runcah. Second phase is the the mixture into stoples and called a meeting to order. treatment of Time during 0, 4, 8 and 12 day. Last phase, silase of fish tested bylaboratoris cover the harsh protein, harsh fat, dusty, harsh fibre and extract substance without nitrogen of according to procedure AOAC (1975). Result of research indicate that treatment of level pickle 12,5, 15 and17,5%o not show the existence of real influence ( p0,05) to harsh protein harsh fat, and harsh fibre.Obstetrical mean silage nutrition fish successively as follows : cruide protein ( 55,32;53,69 and 55,07%); extraceter (3,66;3,64and4,01%); andcruide fibre( 1,07;1,05 and l,l4%). Pursuantto inferentialresearchresult that treatment of addition of level of cabbage pickle sort not influence of quality of silage fishKeyword : pickle, cabbage, silase, fish.